The politics of employment relations in a multinational corporation during crisis. (August 2019) - Clibborn, Stephen
Much progress has been made recognising the importance of power and politics in organisational processes but legal regulatory institutional constraints on actors remain overemphasised in the extant literature. This article provides unique insight into organisational processes during the global economic crisis. The glare of crisis illuminates the negotiated nature of organisational processes and outcomes, demonstrating the range of options available to actors, both within and beyond apparent legal institutional limits. General Motors has received significant publicity for its near collapse, government bailout and restructure through bankruptcy proceedings. During the crisis the company made changes impacting its global workforce. This article tracks three key employment practices from development in the United States headquarters to implementation in the Australian subsidiary in the context of inconsistent local laws. Directives to cut pay for some employees, freeze pay for others and terminate the employment of a large number of workers were received and implemented in the subsidiary in varying and counterintuitive ways. Institutional consistency does not guarantee successful transfer, while even host country legal institutional inconsistency is no guarantee of failure.